Detection of underground utilities below NTU campus - Tan, Ying Cui (Nanyang Technological University, 2023)
Underground utilities are necessary to provide public services. With underground utilities, it resolves the issue of limited land space. However, these utilities are placed under the surface which cannot be seen from the surface of ground. If the underground utilities are broken, they will cut off the supplies of electricity or water supplies. In a more serious extent, it could lead to cavity to form in the subsurface. With the lack of proper management, it has the possibility to cause damage to the underground structures which could pose a threat to the population. Therefore, regular detection of underground is necessary to prevent any damage to the soil structure and facilities. In this project, it focuses on seismic scattering method which uses seismic waves collected to analyze the condition of the underground.